2022
DOI: 10.1186/s12872-022-02684-9
|View full text |Cite
|
Sign up to set email alerts
|

Illness perception and cardiovascular risk factors in patients with myocardial infarction undergoing percutaneous coronary intervention in Iran

Abstract: Background Knowing of perception of the illness, and cardiovascular risk factors in patients with myocardial infarction is crucial in engaging in effective secondary prevention. This study aimed to examine illness perception and cardiovascular risk factors in patients with myocardial infarction undergoing percutaneous coronary intervention. Methods The participants comprised 131 patients undergoing a first-time percutaneous coronary intervention at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…This is similar to the results of previous studies. 47,48 Studies have confirmed that mood affects people's risk perceptions, with people perceiving relatively less risk when in a positive mood and more risk when in a negative mood. 49 Therefore, healthcare workers should identify depressed patients early and enhance attention and intervention for psychological problems.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the results of previous studies. 47,48 Studies have confirmed that mood affects people's risk perceptions, with people perceiving relatively less risk when in a positive mood and more risk when in a negative mood. 49 Therefore, healthcare workers should identify depressed patients early and enhance attention and intervention for psychological problems.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence shows that although CHD patients receive information about risk factors, support is critical for adherence to treatment (Kähkönen et al., 2020; Nicolai et al., 2018; Shi et al., 2022). Patients often perceive the PCI procedure as a curative treatment and that their illness is acute rather than chronic (Ashour et al., 2020); these perceptions have been shown to be associated with adverse outcomes (Thagizadeh et al., 2022) and poor adherence to treatment (Kähkönen et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A lack of social support has related to anxiety and depression (Hu et al, 2022;Thagizadeh et al, 2022;Zhang, 2021), which may affect a person's health indirectly through unhealthy behaviours or directly via physiological mechanisms (Freak-Poli et al, 2022;Hu et al, 2022;Zhang, 2021). For this reason, versatile support is needed during post-PCI recovery.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Studies have shown associations between illness perception and adherence to secondary prevention in patients with coronary heart disease. 20,21…”
mentioning
confidence: 99%